2018
DOI: 10.1080/17524032.2018.1544160
|View full text |Cite
|
Sign up to set email alerts
|

Using Visual Impact Metaphors to Stimulate Environmentally Friendly Behavior: The Roles of Response Efficacy and Evaluative Persuasion Knowledge

Abstract: Although people often are aware of the importance of adopting environmentally friendly lifestyles, they might be reluctant to do so as they believe that their actions do not make a difference (i.e. low response efficacy). Furthermore, they might experience reactance (e.g. negative attitudes) towards environmental messages that encourage them to adopt an environmentally friendly lifestyle. Therefore we experimentally tested whether it is possible to stimulate people to adopt an environmentally friendly lifestyl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
25
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(27 citation statements)
references
References 51 publications
2
25
0
Order By: Relevance
“…Perceived empathy describes users' perception that the PSS can resonate with their feelings (Plank et al , 1996). In existing research, VIMs have been found to be “generally more persuasive than literal arguments” but are less likely to trigger “evaluative persuasive knowledge” in the message recipient (Boerman et al , 2012; Meijers et al , 2019). Therefore, VIMs are less likely to be suspected, more likely to evoke deeper affects and be positively evaluated by the message recipient (Meijers et al , 2019).…”
Section: Research Model and Hypothesis Developmentmentioning
confidence: 99%
See 3 more Smart Citations
“…Perceived empathy describes users' perception that the PSS can resonate with their feelings (Plank et al , 1996). In existing research, VIMs have been found to be “generally more persuasive than literal arguments” but are less likely to trigger “evaluative persuasive knowledge” in the message recipient (Boerman et al , 2012; Meijers et al , 2019). Therefore, VIMs are less likely to be suspected, more likely to evoke deeper affects and be positively evaluated by the message recipient (Meijers et al , 2019).…”
Section: Research Model and Hypothesis Developmentmentioning
confidence: 99%
“…The use of metaphors for information visualization has been extensively researched in the fields of environmental studies, education and advertising (Iacoboni and Dapretto, 2006; Gatsou et al , 2011; Li et al , 2017b; Meijers et al , 2019). Visual metaphors are effective tools for the quick transmission of effective mental models from the mind of one party to another in circumstances like user interface design and information visualization.…”
Section: Theoretical Foundationmentioning
confidence: 99%
See 2 more Smart Citations
“…This important role of metaphors to "translate" new, complex, vague issues into more familiar, simpler, more concrete ones has been already recognised in the context of sustainable living: (a) there is a longstanding theoretical and experimental scholarship seeking to uncover "metaphors [to] survive by" (e.g. Karlsson, 2015;Larson, 2011;Meijers et al, 2018;Norgaard, 1995); and (b) researchers have started analysing metaphor use within business and educational sustainability discourses and within the discourse of proenvironmental citizens, identifying Journey 3 and Limit metaphors as particularly common (Carew & Mitchell, 2006;Milne et al, 2006;Uren et al, 2019). This paper advances research on metaphors and sustainability by exploring the understudied area of how sustainable living 4 is metaphorically presented on top personal green living blogs authored by ordinary individuals.…”
mentioning
confidence: 99%